The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/rs14020321
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Convolutional Neural Network and Conventional Machine Learning Methods for Landslide Susceptibility Mapping

Abstract: Landslide susceptibility mapping (LSM) is a useful tool to estimate the probability of landslide occurrence, providing a scientific basis for natural hazards prevention, land use planning, and economic development in landslide-prone areas. To date, a large number of machine learning methods have been applied to LSM, and recently the advanced convolutional neural network (CNN) has been gradually adopted to enhance the prediction accuracy of LSM. The objective of this study is to introduce a CNN-based model in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 67 publications
0
17
0
1
Order By: Relevance
“…The activation function follows the convolutional layer and Rectified linear unit function is the most popular and effective activation function. The down-sampling layer or pooling layer is used to reduce the size of features, and the over-fitting tendency of the model [60]. DNN is a popular method employed in various natural hazard-related studies.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activation function follows the convolutional layer and Rectified linear unit function is the most popular and effective activation function. The down-sampling layer or pooling layer is used to reduce the size of features, and the over-fitting tendency of the model [60]. DNN is a popular method employed in various natural hazard-related studies.…”
Section: Deep Learning Methodsmentioning
confidence: 99%
“…Liu et al [60] did a comparative study of CNN with conventional ML models. The LSM generated by the CNN-based model is sensitive to the high-risk landslide zone and significantly reduces the salt-and-pepper effect, which guarantees the consistency of susceptibility assessment.…”
Section: Literature On Deep Learning Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the powerful image feature extraction performance of CNNs, they can theoretically be directly applied to landslide susceptibility assessment. For example, Liu et al [160] compared CNNs and traditional machine learning methods for landslide susceptibility mapping and demonstrated that both CNNs and traditional machine learning-based models have satisfactory performance, and CNNs achieved the highest performance. Youssef et al [161] compared SVM, one-dimensional and two-dimensional CNNs and demonstrated that two-dimensional CNNs have the best performance compared to one-dimensional CNNs and SVMs.…”
Section: Landslide Susceptibility Assessmentmentioning
confidence: 99%
“…La exactitud de la prueba aumenta a medida que la curva se desplaza desde la diagonal hacia el vértice superior izquierdo. Un valor mayor indica que el modelo puede lograr un mejor rendimiento (Liu et al, 2022).…”
Section: Modelo De Cnnunclassified